THE USE OF POPULAR “AUTHENTIC” ARTICLES IN THE TEACHING OF ANALYTICAL EXPOSITION WRITING TO ELEVENTH GRADERS IN SMAN 1 SIDOARJO (RETAIN, 2014)
THE USE OF POPULAR “AUTHENTIC” ARTICLES IN THE TEACHING OF ANALYTICAL EXPOSITION WRITING TO ELEVENTH GRADERS IN SMAN 1 SIDOARJO Erina Yuniarni English Education Department, Language and Arts Faculty, Surabaya State University. Email: sizukanaerina@yahoo.co.id Dra. Theresia Kumalarini, M.Pd English Education Department, Language and Arts Faculty, Surabaya State University. Email: kumala_rini52@yahoo.co.id Abstrak “Popular Authentic Articles” memberi inspirasi atau ide-ide yang dapat digunakan untuk menggembangkan kerangka tulisan dan membantu guru dalam pengajaran menulis teks Analytical Exposition. Dengan menggunakan ini, siswa diharapkan dapat menguatkan pendapat mereka tentang beberapa topic berdasarkan informasi yang ditemukan dalam artikel. Penelitian ini bertujuan untuk melihat bagaimana penggunaan dan respond siswa terhadap penggunaan “Popular Authentic Articles”. Metode penelitian yang di gunakan adalah descriptif kualitatif. Instrumen yang telah digunakan untuk mengumpulkan data adalah catatan kaki, Laporan observasi dan pertanyaan. Subjek dalam penelitian ini adalah guru bahasa Inggris dan siswa kelas XI sekolah menengah atas di SMA Negeri 1 Sidoarjo, yang diwakili oleh kelas IPA 9. Hasil penelitian menunjukan ada tujuh tahap yang dibutuhkan untuk digunakan dalam proses pengajaran menggunakan “Popular Authentic Articles”. Langkah-langkah tersebut adalah memberikan curah pendapat, mendiskusikan arti dari kosakata sulit. Membuat sesi tanya-jawab berhubungan dengan isu, mengembangkan proses pembuatan outline. Memandu siswa dalam aktivitas menulis, ,memberi umpan balik di tulisan siswa dan meminta mereka memperbaiki. Selanjutnya, penggunaan media ini berhasil membantu siswa dalam menemukan ide-ide, menguatkan argument, meningkatkan motivasi, serta antusiame mereka dalam menulis teks analytical exposition. Kata kunci: ‘Popular authentic articles’, Menulis, Analytical Exposition, Sekolah Menengah Atas. Abstract “Popular authentic articles” as a media gives inspirations or ideas that can be used in developing written form and helps the teacher in teaching writing, especially in teaching of analytical exposition writing. By using it, the students are expected to be able to reinforce their arguments on a certain topic based on some information that are found in the articles. This study aims to see how the use and the students’ respond toward the use of “Popular Authentic Articles”. The method of this research was descriptive qualitative. The instruments that were used to collect the data were field notes, observation checklist and a questionnaire. The subjects of this study were the English teacher and the eleventh graders of senior high school in SMA Negeri 1 Sidoarjo, which was represented by class 9 of science program. The result showed that there were seven stages that were needed to be taken in the teaching process using “Popular Authentic Articles”. Those steps were giving brainstorming, discussing the meaning of difficult words, making a dialogue session related to the issues, developing the process of making an outlines, guiding the students in their writing activity, giving feedback in the students writing and asking the students to revise it. In addition, it also showed that the use of “Popular Authentic Article” succeeded in helping the students to find ideas to reinforce their argument and enhance their motivation and enthusiasm in writing analytical exposition text. Key words: Popular Authentic Articles, Teaching writing, Analytical exposition, Senior high school. INTRODUCTION The 2006 standard competency (BSNP, 2006) states that teaching English in senior high school level aims to enable students to reach the informational level because students are being prepared to continue their education to the university. The language skills taught comprise listening, speaking reading, and writing. One of the skills that students should be mastered is writing. Students are expected to write their ideas and communicate their language using words. Nunan (1991) stated writing is the mental work of inventing ideas, thinking of how to express ideas, and organizing them into statements and paragraphs until it is clearer to the reader. In writing an analytical exposition text, the students should be able to argue their arguments about a case in written form systematically. Anderson (1997) stated that It usually has there sections. First, introduces the reader a point of view. Then, give series of argument to convince the audience. The last is conclusion that reinforces the author’s point of view. Unfortunately, the teaching process of analytical exposition text is not an easy matter. Sometimes, the English teacher faces a problem in choosing a suitable technique, and the media in the teaching writing of analytical exposition. To overcome those problems, teachers should try to use some techniques or media which can help students in their writing. In this study, the researcher purposes “popular authentic articles” as an alternative media to teach analytical exposition writing. It is based on the belief that popular authentic articles will help the teacher to reduce the boredom of students, enhance the students’ motivation in writing and also help students to develop their ideas and the content of writing. The use of “popular authentic articles” as an alternative media in teaching analytical exposition writing is still rare. By using “popular authentic articles”, students are expected to be able to reinforce their arguments about a certain topic based on some information that is found in the articles. “Popular authentic articles” provide students with exposure to real usage and culture of target language. Learning foreign language means learn their culture as well. “Popular authentic articles” contain both popular issues and some information and evidences to help students in supporting their argument. “Popular Authentic Articles” as a media gives inspirations or ideas that can be used in developing a written form. Besides that, it helps students to be interested and enjoy in the learning process because it is assumed that students will have no difficulty in gathering information about the topic. By reading them the students can find the new knowledge. In a learning context, students can express their experiences which are combined with the issues in the articles into analytical exposition text in written form. Started from the ideas above, the researcher assumes it is important to make a descriptive study of analytical exposition writing. This study aims to see the stages of using “Popular Authentic Articles” in senior high classrooms. In addition, this study is beneficial to see the students respond toward the use of “Popular Authentic Articles”. Thus, many teachers will understand the correct stages in using “Popular Authentic Articles” and will see the students’ respond toward the use of media. The object of the study will be the eleventh grade students of Senior High School METHOD The research design in this study is descriptive qualitative. It is used to answer the questions and to obtain the information related to the use of popular authentic articles as a teaching media in helping Eleventh graders of senior high school in SMA Negeri 1 Sidoarjo to write the analytical exposition text. The subjects of this study were the English teacher and the Eleventh grader of senior high school in SMA Negeri 1 Sidoarjo, which was represented by class 9 of science program. The researcher used field notes, checklist and questionnaire as instrument to conduct the research. The data for answering the first question were taken from transcription of observation in the teaching and learning process. Transcription explained about the teaching and learning process. It was taken from observation checklist and field note. Observation checklist covered point of observation in teaching process conducted by the teacher and learning process of students. Therefore field note covered information data’s transcription. Meanwhile for the second question the data were taken from questionnaire. It concerned the students’ feeling toward the use of popular authentic articles in the learning of analytical exposition writing. In gathering this data, the researcher distributed a questionnaire sheet to all of the students. The researcher did a non-participant observation as a technique to collect the data needed to answer the research questions. in non participant observation which the researcher did not involved in the process of teaching and learning (Susanto, 2000) It discusses the answers to the research questions in how the use of popular authentic articles as a teaching media in teaching writing analytical exposition text is like and how the students’ responses toward the use of “popular authentic articles” as a teaching media are like. RESULT AND DISCUSSION Result Firstly, the researcher will describe the result of field notes, the result of checklist and the result of questionnaire. In the result of field notes, on first observation before the researcher attended the class, the teacher showed the plan of learning activity to the researcher. She told that most students of class 9 of science program are smart students. They followed learning process actively and had high motivation to learn English. The teacher greeted the students and let the researcher introduced herself to the students in the class. The teacher informed them that the researcher would be in the class for three meetings to observe the teaching and learning process. Pre learning activity, In this stage, the teacher began the activity by holding a brain storming dialogue with the students. Whilst learning Activity, In this stage after holding the brain storming dialogue; the teacher distributed the copies of the first article, entitle “should kids have phones at school?” to the students and instructed them to read the article for a while. After that, the teacher answered the students’ questions about the meaning of difficult words from the text. Then, the teacher instructed the students to read the article once more. The teacher divided the class into pros and cons, then she asked them to write an outline then continued it by developing their outline into completed analytical exposition text. After that, the teacher supervised the students and helped them in their writing. Post learning Activity, In this stage, the teacher asked the students to collect their writing product. On the Second observation, As the previous observation, the teacher showed the plan of learning activity to the researcher before entered the classroom. The teacher did not do warming activity in the second meeting. This was due to limited time because the students had a biology daily exam after this lesson. She began the main main activity by giving back the students’ writing products in the previous meeting which were completed by feedback notes from the teacher. After that, the teacher asked the students to pay atention to the teacher’s explanation and correction then she asked the students to revise their own writings. Several minutes before the class ended, the teacher asked the students to submit their writting and asked the students’ about their difficulties during the teaching and learning process on tha day. Then, she ended the class. On the Third observation, the teacher greeted the students and checked the students’ attendance. The teacher informed to the students about the goal on that day. Then, she started the main activity which included the implementation stages of using “Popular Authentic Articles” in the classroom. These stages were divided into three. Pre learning activity, at this stage, the teacher began the activity by making a brainstorming dialogue about the students’ experience related to the social media on education. Whilst learning Activity, at this stage, after holding the brain storming dialogue, the teacher gave the students the copies of the second article entitled “the effect of social media on education” then she instructed them to read the article for a while. After that, the teacher and the students’ had a dialogue about the meaning of the difficult words, important information and main topic from the text. Then the teacher instructed the students to read the article once more. These activities were followed by a question and answer session about the main issue, the title and in the information written in the article.. After that, the teacher divided the class into pros and cons group. Then, she asked the students to write an outline then continued it by developing their outlines into a complete text. The teacher helped the students in their writing activity. Post learning Activity, at this stage, the students submitted their writing products. Finally, the teacher asked the students difficulties during the learning process. Next, the researcher will describe the result of observation checklist, this observation was conducted on November 25th and 27th and December2nd, 2013. It was taken during the teaching and learning process in the class. The researcher gave tick mark if subject of the study correlated with the activities described in the indicators. The last , the researcher will describe the result of the questionnaire which answers the second research question; the students’ respond toward the use of “Popular Authentic Article” as a media in teaching analytical exposition text. The researcher used a questionnaire to know the students’ response toward the use of ‘popular authentic article” in the teaching of analytical exposition writing. There are 6 questions in the questionnaire, Questions 1 and 2 related to the students’ responses in the teaching process using “popular authentic article” (indicator 1). Questions 3 and 4 was related to the students’ interest in the use of “Popular Authentic Articles” as a media in learning Analytical exposition text (indicator 2). Questions 5 and 6 were to know the students’ opinion about the issues presented in the article (indicator 3). The researcher got the data related to indicator 1 about the students’ responses in the teaching process using “Popular Authentic Article”. Question 1 showed that most of the students were liked enough in the use of popular authentic article in the teaching process. Question 2 showed that most of the students were liked enough in the use of “Popular Authentic Article” in the teaching process. The data related to indicator 2 about the use of media in learning process. Question 3 showed that most of the students were liked enough in the use of “Popular Authentic Article” as a media in learning Analytical exposition text. Question 4 showed that a half of students were helped in the use of “Popular Authentic Article” as a media to help them in writing Analytical exposition text. Question 5 showed that most of the students understood enough about the purpose of the Article that the teacher used. Question 6 showed that most of the students were interested about the topic of the Article that the teacher used. Discussion In this part, the researcher will discuss the result of the research in the relation of the theory. In the first meeting, during pre learning activity, the teacher began doing a brainstorming by asking the students’ opinion about the issues. In whilst learning activity the teacher answered the students’ questions about the meaning of difficult words and some important information from the text. It was important to prevent the students from misunderstanding the text. Making an outline is important to help the students organize and shape their writing. In the post learning activity, the teacher asked the students to submit their work. In the second meeting, the teacher began the main activity by giving back the students’ writing products that were completed by feedback notes from the teacher. It was important to help them improve their writing by knowing their mistakes. After that the teacher gave explanation and correction about the mistakes of the students’ writing products. She asked the students to revise their own writings. Revising was important to improve the students’ skill by showing their mistakes. It is in line with Nunan (1991) who stated that a few principles for teaching writing that every teacher should considered, point three and four. To make helpful and meaningful feedback teacher should gives feedback in the students work to help the students improving their ability in writing and to clarify for the teacher and the students how the writing will be evaluated It should develops a statement about what is valued in student’s writing. In the third meeting, by overviewing the first meeting the teacher added some stages to make the teaching process better. Here are the stages that teacher added: before entering the pre leraning activity she told the students about the goal on that day. It was meant to help the students predict what they would do, then in whilst learning activity she made a question and answer session about the main issue, the title and the information written in the article. This session aimed to help the students understand the content of the text better. And the last in the post learning activity the teacher asked the students’ difficulties about the lesson. It was meant to improve teaching activity by knowing the students’ needs and difficulties. According to the discussion above, there were seven stages that needed to be taken in the teaching process using “Popular Authentic Articles” to the eleventh graders. Those steps are: giving brainstorming, discussing the meaning of difficult words, making a dialogue session related to the issues, developing the process of making an outlines, guiding the students in their writing activity, giving feedback in the students writing and the last asking the students to revise it. Based on the results of the questionnaires that were given to 30 students, it was found out that the students showed positive responses. The researcher found that more than most of the students answered options A and B for questions 1, 2, 3, 5 and 6. Those options indicated that the media helped to find the ideas to write an analytical exposition text (see appendix 3). In conclusion, the students’ response to the use of “Popular Authentic Articles” as a teaching media was satisfied. This finding showed that the use of “Popular Authentic Article” in the teaching of analytical exposition writing to the eleventh graders of SMA N 1 Sidoarjo was given a positive response from the students. “Popular Authentic Article” succeeded in helping the students to find the ideas to reinforce their argument and enhance the students’ motivation and enthusiasm in writing analytical exposition text. CONCLUSION AND SUGGESTION Conclusion The result showed that the use of “Popular Authentic Articles” as a media in the teaching process of analytical exposition writing to the Eleventh graders of SMA N 1 Sidoarjo needs seven stages to be taken. Those steps are; giving brainstorming, discussing the meaning of difficult words, making dialogue session related to the issues, developing the process of making an outlines, guiding the students in their writing activity, giving feedback in the students writing and asking the students to revise it. “Popular Authentic Article” succeeded in helping the students to find the ideas to reinforce their argument and enhance the students’ motivation and enthusiasm in writing analytical exposition text. Suggestion After explaining the results of this research and drawing conclusions, it is suggested to choose the suitable media and attractive material for teenagers, it helps to enhance the their attention and motivation to read and the teacher should write some difficult words in the article to optimize the time. REFFERENCESS Anderson, Mark, & Anderson, a. K. (1997). Text Type In English Vol. 2. Macmillan Education Australia PTY LTD: South Yarra. Berardo, & Sacha. (2006). The use of Authentic Material in Teaching Reading. [online]. The Reading Matrix, 6, 60-69. Brown, H. D. (Ed.). (2001). Teaching by Principle: An Interactive Approach to Language Pendagogy. New York: Longman. Depdiknas. (2006). Kurikulum tingkat satuan pendidikan SMA dan MA Jakarta: Depdiknas. Depdiknas. (2007). Kurikulum Sekolah Menengah Pertama Bertaraf Internasional (SMP-SBI) Jakarta: Depdiknas. Gebhard, J. (Ed.). (2000). Teaching English as a Foreign or Second Language: A Teacher Self-development and methodology Guide. Michigan: The University of Michigan Press. Harmer, & Jeremy. (2001). The Practice of English Language Teaching Nunan, & David. (1991). Language Taeching Methodology: A Text Book For Teacher (pp. 88). United States of America: Prentice Hall International Ltd. Nunan, & David. (2003). Practical English Language Teaching, 1st edited, Pearson Education: New York Nuttal, & Christine. (1996 ). Teaching Reading Skills in a Foreign Language-New Edition, Macmillan Publisher Limited: Oxford O'Malley, & Valdes, P. (Eds.). (1996). Authentic Assesmrnt for English Languge Learner. USA: Addison Wesley Publishing Company. Rahmawati, e. (2010). the popular authentic articles to help teaching hortatory exposition. universitas negeri surabaya. sokolik, & maggie (Eds.). (2003). Chapter Five : Writing in D. Nunan (Ed) Practical English LanguageTeaching. Boston: Mc Graw Hill. Tamo, D. (2009). The Use of Authentic Materials in Classrooms. Article 9 in LCPJ, 2 /1.